Covalent triazine framework (CTF-0) surface as a smart sensing material for the detection of CWAs and industrial pollutants. (1st March 2022) - Sarfaraz, Sehrish; Yar, Muhammad; Ayub, Khurshid
Abstract: Covalent triazine framework (CTF-0) is explored as electrochemical sensor against chemical warfare agents (diphosgene, phosgene oxime) and industrial pollutants (HCN, H2 S, NH3 ). The selectivity, sensitivity, and the adsorption properties of CTF-0 for selected analytes are investigated through symmetry perturbation theory (SAPT0), non-covalent interaction (NCI), and quantum theory of atom in molecule (QTAIM) analyses. The results indicated that all the analytes are weakly physiosorbed on the surface of CTF-0. The adsorption of analytes on CTF-0 follows the trend: PhO@CTF-0 > DPh@CTF-0 > HCN@CTF-0 > H2 S@CTF-0 > NH3 @CTF-0. Electronic properties of selected analytes@CTF-0 complexes are evaluated through EDD, NBO, FMO and DOS analysis. Appreciable charge transfer is observed from surface to analytes, except for DPh@CTF-0 complex where charge is transferred from analyte to surface. The highest interaction energy is observed for PhO@CTF-0 (−11.19 kcal/mol), which is consistent with the results of SAPT0 and EDD analysis. FMO results revealed that the highest decrease in EH-L gap is observed for H2 S@CTF-0. Overall, results indicate that, among all five analytes, CTF-0 surface is more sensitive towards H2 S. Graphical abstract: Image 1 Highlights: CTF-0 surface is studied for the detection of chemical warfare agents and industrial effluents. Nature of interactions between analyte and surface is demonstrated through NCI, SAPT0 and QTAIM analysis. CTF-0 surface is highly selective towards H2 S analyte as compared to other studied analytes. CTF-0 is promising sensor for harmful industrial pollutants and toxic chemical molecules.